Knowledge, Attitude, and Prevalence Towards Cervical Cancer Screening Among Women in a Nigerian Urban Municipality - Daniel, Faithful Miebaka; Ike, Williams Ibangha; Gbuchie Anurika, Monica; Udofia James, Saviour; Chinyere Kalu, Perfection; Ebizo Ikpa, Sunday (International Journal of Medical Students, 2023)
BACKGROUND: Cervical cancer is a significant global health concern, particularly in less developed regions, ranking as the fourth most common cancer among women. Nigeria faces its crisis, with approximately 15,000 women diagnosed annually, resulting in a two-thirds fatality rate. An alarming 40 million Nigerian women remain at risk, underscoring the urgency of improved screening and disease surveillance, compounded by the absence of a national cancer policy and limited awareness. Cervical cancer can be reduced by more than 90% through regular screening. It is caused by sexually transmitted HPV and risk factors include multiple sexual partners, smoking, long-term oral contraceptive use, and immunosuppression. AIM: The study aimed to ascertain the knowledge, attitude, and practices toward cervical cancer screening and the factors that influence the practice of screening among women of the reproductive age group in Calabar Municipality. METHODS: Using a cross-sectional study design, 414 women were enrolled from two public hospitals, four private hospitals, and a non-governmental women’s center through a meticulous multi-stage sampling technique, employing semi-structured questionnaires. Socio-demographic variables were collected, and a 31-item questionnaire was used to assess the level of knowledge, attitudes, and practices toward cervical cancer. Data were analyzed using IBM SPSS version 26; p-values less than 0.05 were considered significant. RESULTS: The mean ages of respondents were 28.01 ± ((8.8357), 293 were single, while 107 were married. 69.67% had received at least tertiary education. 51.9% were employed, and the rest were unemployed. All 414 respondents were familiar with cervical cancer, but 65.7% lacked adequate knowledge of screening. Approximately 60% were aware of screening tests, with health workers as their primary information source. Most women displayed a favorable attitude toward screening; 97.3% expressed willingness if the procedure was explained and accessible, 96.4% if it was free and safe, and 97.6% supported screening for women under 30 years. Unfortunately, only 8% had undergone screening, with Pap smears as the commonest screening method for 84.8% of those who had received screening. Out of 381 respondents who had never been screened, 101 did not think they were at risk, 89 did not know where to get screened, 75 believed their religion protected them, and 37 found it expensive. In bivariate analysis, age, marital status, employment status, and knowledge of screening significantly correlated with good practice (p<0.05). CONCLUSION: The underutilization of screening services in an urban setting is concerning, signaling the potential for cancer care disparities in rural areas. Urgent interventions are needed to foster more favorable attitudes and practices, particularly in developing countries like Nigeria, where cervical cancer remains a leading women’s health concern. With Nigeria’s limited healthcare financing and fragile health system, cervical cancer screening promotion is crucial. Community-based strategies should be utilized to promote screening, and medical outreaches organized to eliminate healthcare barriers. The government should increase funding for the health sector and provide more screening centers while empowering healthcare providers.